Internationalization process of Russian construction industry: Inward investments perspective - Andrej Ju. Panibratov (Journal for East European Management Studies, 2009)
Inward investments as the cornerstone of the entry mode choice are still considered a frontier issue within the field of internationalization - as judged from the academic interest as well as from the numerous articles published in scientific journals. Despite considerable progress in later years in formulation of theories, many weaknesses still exist within this field. A further development of theory is therefore needed. Nowadays emerging markets show the greatest activity in the field of internationalization, e.g the Russian market, which is considered by most potential entrants as a huge opportunity. The methods of entry and models of operations of international contractors in the Russian market, based on the investment decisions, are investigated in this paper. – – Direktinvestitionen als Eckpfeiler für den Markteintritt werden weiterhin als Randgebiet der Internationalisierung angesehen - sowohl vom akademischen Interesse her als auch in den veröffentlichten Artikeln der Fachliteratur. Trotz beträchtlicher Fortschritte in den letzten Jahren bei der Formulierung von Theorien existieren immer noch viele Schwächen innerhalb dieses Feldes. Deshalb ist eine weitere Theorieentwicklung notwendig. Heutzutage weisen die 'emerging markets' die stärksten Aktivitäten im Bereich der Internationalisierung, beispielsweise der russische Markt, der von den meisten potenziellen Marktteilnehmern als eine enorme Gelegenheit angesehen wird. Die Methoden des Eintritts und die Modelle der Kooperation der internationalen Anbieter auf dem russischen Markt werden, basierend auf ihrer Investitionsentscheidung, in diesem Beitrag untersucht.
Keywords: 650; internationalization; entry mode; foreign direct investment; construction industry; Russia